Health Education Teaching Materials Through Comic Media for Primary School Students - Sudarmono, Martin; Hanani, Endang Sri (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Background: Teaching media is one of several instruments used by teachers to help them carry out the teaching and learning. However, based on the results of the preliminary study, only 30% of primary schools use learning media. Methods: This study is developmental research. The development procedures in this study include: (1) conducting a need analysis, (2) making a draft of the initial product, (3) validating experts, (4) improving the draft initial product, (5) first trial, (6) initial product revisions, (7) second trial, (8) revision of final products and (9) final products of the health education teaching materials. Results: This study obtained 85% of health education experts evaluation data and 95% of media experts so that the average percentage was 90% and included in the